TAM receptors Tyro3 and Mer as novel targets in colorectal cancer - Schmitz, Robin; Freire Valls, Aida; Yerbes, Rosario; Richter, Sophie von; Kahlert, Christoph; Loges, Sonja; Weitz, Jürgen; Schneider, Martin; Ruiz de Almodóvar, Carmen; Ulrich, Alexis; Schmidt, Thomas (OncoTarget, 2016)
CRC remains the third most common cancer worldwide with a high 5-year mortality rate in advanced cases. Combined with chemotherapy, targeted therapy is an additional treatment option. However as CRC still escapes targeted therapy the vigorous search for new targets is warranted to increase patients´ overall survival.